O estudo dos números complexos no ensino médio: uma abordagem com a utilização do Geogebra - Amorim, Tânia Mara (2014)
This work aimed to facilitate the study of the content of complex numbers for students in the 3rd year of High School, within a focus covering a geometric context, with the use of Geogebra software, combined with notebook student (SÃO PAULO, 2014). The main motivation of this study was to search for an innovative practice, aiming to improve the quality of the teaching-learning process, in relation to the content, since the numerous difficulties demonstrated by students. The theoretical research was based mainly on the theory of representation semiotics registers of Raymond Duval and analysis of curriculum documents for Middle School. Already the methodology was built based on the steps of the Didactics Engineering idealized by Michele Artigue. The production of information involved mathematical activities performed by 31 students of Higher Education of a Civil Engineering course and between 10 to 12 students (there was variation) of a 3rd year of High School; providing the basis for answering the following research issues: I What knowledge about complex numbers, students of Higher Education bring the baggage of high School? II - That prospect of construction of knowledge the notebook of the Student gives the learning of complex numbers? III - The Geogebra can add the construction of knowledge when articulated to the notebook of the Student, made available by the Department of the São Paulo State of Education? The instruments used to collect the amount of information produced by participants, in empirical step of our research were: questionnaire, written records of tasks (protocols) and images of mathematical activities carried out with the help of Geogebra. The results obtained in the analysis of the questionnaires showed that the knowledge of the students in higher education, as well as the students in the middle school, are negligible in relation to the need of those who follow their studies in the field of exact area. With respect to the results obtained from the implementation of tasks for high school students, using the software proved to be efficient for a geometrized viewing the content in relation to construction of its concepts, which allowed students a much better understanding across the studied content.